2018
DOI: 10.1523/jneurosci.3195-17.2018
|View full text |Cite
|
Sign up to set email alerts
|

Hyperactivity of Anterior Cingulate Cortex Areas 24a/24b Drives Chronic Pain-Induced Anxiodepressive-like Consequences

Abstract: Pain associates both sensory and emotional aversive components, and often leads to anxiety and depression when it becomes chronic. Here, we characterized, in a mouse model, the long-term development of these sensory and aversive components as well as anxiodepressive-like consequences of neuropathic pain and determined their electrophysiological impact on the anterior cingulate cortex (ACC, cortical areas 24a/24b). We show that these symptoms of neuropathic pain evolve and recover in different time courses foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
153
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 167 publications
(168 citation statements)
references
References 46 publications
12
153
2
1
Order By: Relevance
“…It has been suggested that ACC mainly plays a role in the affective (or aversive) component of pain. Several research groups, using multiple pain conditions and interventions, have shown that ACC excitation correlates with increased aversive responses to pain (LaGraize et al, 2004;LaGraize and Fuchs, 2007;Qu et al, 2011;Navratilova et al, 2015;Sellmeijer et al, 2018). Therefore, we tested whether ASIC1a in the ACC contributes to pain-related negative affect.…”
Section: Blocking Asic1a In Acc Reverses Established Pain Hypersensitmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been suggested that ACC mainly plays a role in the affective (or aversive) component of pain. Several research groups, using multiple pain conditions and interventions, have shown that ACC excitation correlates with increased aversive responses to pain (LaGraize et al, 2004;LaGraize and Fuchs, 2007;Qu et al, 2011;Navratilova et al, 2015;Sellmeijer et al, 2018). Therefore, we tested whether ASIC1a in the ACC contributes to pain-related negative affect.…”
Section: Blocking Asic1a In Acc Reverses Established Pain Hypersensitmentioning
confidence: 99%
“…We next asked whether there is any cell type-related difference for the involvement of ASIC1a in pain hypersensitivity. Previous optogenetic studies have revealed that excitatory neurons are main contributors in ACC that modulate pain perception (Kang et al, 2015;Sellmeijer et al, 2018). Therefore, we first specifically knocked out ASIC1a in ACC excitatory neurons, by injecting AAV driven by the CaMKII promoter for excitatory neuron-specific Cre recombinase expression (AAV-CaMKII-Cre) into the ACC of ASIC1a flox/flox mice ( Fig.…”
Section: Asic1a In Excitatory Neurons Of Acc Is the Major Player In Lmentioning
confidence: 99%
See 1 more Smart Citation
“…Lesions of the ACC prevent the development of anxiodepressive behaviors without affecting hypersensitivity symptoms, whereas optogenetic activation of the ACC promotes depressive states (122). A study by Sellmeijer et al applied the cuff model of peripheral nerve injury to demonstrate a potent role of the ACC in modulating anxiodepressive behaviors (123). Using in vivo electrophysiological recordings, the investigators observed an increased firing rate and bursting activity within the ACC at time points at which anxiety and depression-like behaviors had developed (123).…”
Section: Studies On Neuronal Circuitsmentioning
confidence: 99%
“…A study by Sellmeijer et al applied the cuff model of peripheral nerve injury to demonstrate a potent role of the ACC in modulating anxiodepressive behaviors (123). Using in vivo electrophysiological recordings, the investigators observed an increased firing rate and bursting activity within the ACC at time points at which anxiety and depression-like behaviors had developed (123).…”
Section: Studies On Neuronal Circuitsmentioning
confidence: 99%